ROS and Sympathetically Mediated Mitochondria Activation in Brown Adipose Tissue Contribute to Methamphetamine-Induced Hyperthermia - Sanchez-Alavez, Manuel; Conti, Bruno; Wood, Malcolm R.; Bortell, Nikki; Bustamante, Eduardo A.; Saez, Enrique; Fox, Howard S.; Marcondes, Maria Cecilia G. (Frontiers in Endocrinology, 2013)
Methamphetamine abuse has been shown to induce alterations in mitochondrial function in the brain as well as to induce hyperthermia, which contributes to neurotoxicity and Meth-associated mortality. Brown adipose tissue (BAT), a thermogenic site known to be important in neonates, has recently regained importance since being identified in significant amounts and in correlation with metabolic balance in human adults. Given the high mitochondrial content of BAT and its role in thermogenesis, we aimed to investigate whether BAT plays any role in the development of Meth-induced hyperthermia. By ablating or denervating BAT, we identified a partial contribution of this organ to Meth-induced hyperthermia. BAT ablation decreased temperature by 0.5oC and reduced the length of hyperthermia by 1 hr, compared to sham-operated controls. BAT denervation also affected the development of hyperthermia in correlation with decreased the expression of electron transport chain molecules, and increase on PCG1a levels, but without affecting Meth-induced UCP1 upregulation. Furthermore, in isolated BAT cells in culture, Meth, but not Norepinephrine (NE), induced H2O2 upregulation. In addition, we found that in vivo Reactive Oxygen Species (ROS) play a role in Meth hyperthermia. Thus, sympathetically- mediated mitochondrial activation in the BAT and Meth-induced ROS are key components to the development of hyperthermia in Meth abuse.